Radiographic abnormalities in the thoracolumbar spine of young elite skiers - Rachbauer, F.; Sterzinger, W.; Eibl, G. (The American Journal of Sports Medicine, 2001)
An increased frequency of radiologic abnormalities in the thoracolumbar spine has been reported among young athletes in various sports, but there are no data concerning ski sports. To evaluate the incidence of these abnormalities in young elite skiers, we compared 120 skiers younger than 17 years old (alpine skiers, ski jumpers, and Nordic cross-country skiers) with a random sample of 39 control subjects of the same age who had no history of high-performance sports participation. Standardized anteroposterior and lateral radiographs of the entire lumbar spine, the lower thoracic spine, and the upper part of the sacrum were obtained from each athlete and each control subject. Radiographs were evaluated by two independent observers for the presence and size of anterior and posterior endplate lesions and Schmorl's nodes. The elite alpine skiers and ski jumpers demonstrated a significantly higher rate of anterior endplate lesions than did the control subjects. This finding might be attributable to excessive loading and repetitive trauma of the immature spine under high velocity, especially in the forward bent posture.